Rare X Chromosome Abnormalities in Systemic Lupus Erythematosus and Sjögren's Syndrome. Issue 11 (12th October 2017) - Sharma, Rohan; Harris, Valerie M.; Cavett, Joshua; Kurien, Biji T.; Liu, Ke; Koelsch, Kristi A.; Fayaaz, Anum; Chaudhari, Kaustubh S.; Radfar, Lida; Lewis, David; Stone, Donald U.; Kaufman, C. Erick; et al.
Abstract : Objective: Sjögren's syndrome (SS) and systemic lupus erythematosus (SLE) are related by clinical and serologic manifestations as well as genetic risks. Both diseases are more commonly found in women than in men, at a ratio of 10 to 1. Common X chromosome aneuploidies, 47, XXY and 47, XXX, are enriched among men and women, respectively, in either disease, suggesting a dose effect on the X chromosome. Methods: We examined cohorts of SS and SLE patients by constructing intensity plots of X chromosome single‐nucleotide polymorphism alleles, along with determining the karyotype of selected patients. Results: Among 2, 500 women with SLE, we found 3 patients with a triple mosaic, consisting of 45, X/46, XX/47, XXX. Among 2, 100 women with SS, 1 patient had 45, X/46, XX/47, XXX, with a triplication of the distal p arm of the X chromosome in the 47, XXX cells. Neither the triple mosaic nor the partial triplication was found among the controls. In another SS cohort, we found a mother/daughter pair with partial triplication of this same region of the X chromosome. The triple mosaic occurs in 1 in 25, 000–50, 000 live female births, while partial triplications are even rarer. Conclusion: Very rare X chromosome abnormalities are present among patients with either SS or SLE and may inform the location of a gene(s) that mediates an X dose effect, as well as critical cell types in which such an effect is operative.